LGBTQ MEANING CONSTRUCTION ON THE #FREETOLOVE CAMPAIGN IN CLOSE UP ADVERTISEMENT: LGBTQ+ CONSTRUCTION ON THE #FREETOLOVE CAMPAIGN - Gusfa, Henni; Ramdani; Franciska, Stella Monica (Revista Prâksis, 2021)
The purpose of this study was to investigate the meaning construction of the signs contained in the #FreetoLove campaign in the Close Up advertisement that constructs LGBTQ. This study applied Ferdinand De Saussure’s Semiotic Analysis Method in analysing the data. The analysis deeply discussed the concept of #FreetoLove campaign from Close Up advertisement and the appearance of signs in it which was considered to construct the Lesbian, Gay, Bisexual, Transgender, and Queer (LGBTQ) meaning in Indonesian version of Close Up advertisement. The advertisement was created in two versions to which one was commercialised globally and the other was for countries whose culture went against LGBTQ. By applying De Saussure analysis, the result showed that non-LGBTQ advertisement of Close up # freetolove adopted LGBTQ signs into the setting of the advertisement. The signs being used were bright colors resembling LGBTQ community, stripe-pattern, and green carnation as the old symbol of gay people.